TNF-α enhances sensory DRG neuron excitability through modulation of P2X3 receptors in an acute colitis model - Valdez-Morales, Eduardo E.; Sánchez-Navarro, Carlos A.; Reyes-Pavón, Diana; Barrios-Garcia, Tonatiuh; Ochoa-Cortes, Fernando; Barajas-Espinosa, Alma; Barragán-Iglesias, Paulino; Guerrero-Alba, Raquel (Frontiers in Immunology, 2022)
Previous studies have demonstrated that acute colonic inflammation leads to an increase in dorsal root ganglia (DRG) neuronal excitability. However, the signaling elements implicated in this hyperexcitability have yet to be fully unraveled. Extracellular adenosine 5’-triphosphate (ATP) is a well-recognized sensory signaling molecule that enhances the nociceptive response after inflammation through activation of P2X3 receptors, which are expressed mainly by peripheral sensory neurons. The aim of this study is to continue investigating how P2X3 affects neuronal hypersensitivity in an acute colitis animal model. To achieve this, DNBS (Dinitrobenzene sulfonic acid; 200 mg/kg) was intrarectally administered to C57BL/6 mice, and inflammation severity was assessed according to the following parameters: weight loss, macroscopic and microscopic scores. Perforated patch clamp technique was used to evaluate neuronal excitability via measuring changes in rheobase and action potential firing in T8-L1 DRG neurons. A-317491, a well-established potent and selective P2X3 receptor antagonist, served to dissect their contribution to recorded responses. Protein expression of P2X3 receptors in DRG was evaluated by western blotting and immunofluorescence. Four days post-DNBS administration, colons were processed for histological analyses of ulceration, crypt morphology, goblet cell density, and immune cell infiltration. DRG neurons from DNBS-treated mice were significantly more excitable compared with controls; these changes correlated with increased P2X3 receptor expression. Furthermore, TNF-α mRNA expression was also significantly higher in inflamed colons compared to controls. Incubation of control DRG neurons with TNF-α resulted in similar cell hyperexcitability as measured in DNBS-derived neurons. The selective P2X3 receptor antagonist, A-317491, blocked the TNF-α-induced effect. These results support the hypothesis that TNF-α enhances colon-innervating DRG neuron excitability via modulation of P2X3 receptor activity.